Automated Plant Viability System for Early Detection of Plant Disease. Issue 16 (2016) - Navaei, Milad; Hesketh, Peter J.; Mahdavifar, Alireza; McMurray, Gary
Abstract: This paper reports on the design and implementation of a plant viability sensor system based on micro fabrication and wireless communication technologies. The system consists of a Solid Phase Micro-extraction (SPME) Injector, a gas chromatography column with OV-1 coating, a low power thermal conductivity sensor, and a circuit design. The system uses the SPME injection method which allows injection of small amounts of analytes into the GC system instantly. The column with a 2 dimensional temperature programming provides a better separation of the volatile compounds and the CMOS TCD sensors provides high resolution for detection of a low concentration. A 12 bit microcontroller with a low noise circuit system and a Bluetooth communication technology are implemented for live monitoring of the VOC gases. The documented performance shows that the system is able to detect and transmit the volatile organic compounds of interest to a handheld device.